Lenguaje oral en estudiantes de 5 años expuestos y no expuestos a contaminación plúmbica - Callao - Neyra López, Carolina Amelia (2012)
The purpose of this research was to determine the differences in oral language development in children exposed and not exposed to lead contamination. These children were assessed with the Test of Oral Language, which is an adaptation of Cárdenas and Neyra (2011) Test of Oral Language Assessment - ELO (Ramos, Cuadrado y Fernandez). The sample consisted of 120 children under 5 years old, 6 students preschool institutions cater characterized by low socioeconomic population. The results show that there are significant differences in the level of oral language development among children exposed and not exposed to lead contamination. It suggests developing more research regarding phonological, semantic and syntactic oral language in children exposed to lead, in order to deepen this theme is to have better tools pedagogical work with these children.